Pemberdayaan Purna TKW (Tenaga Kerja Wanita) Kecamatan Solokuro, Lamongan - Mochamad Mochklas; Achmad Hariri (Universitas Mathla'ul Anwar Banten, 2019)
EMPOWERMENT OF FEMALE MIGRANT WORKERS RETIREMENT OF SOLOKURO DISTRICT, LAMONGAN. Solokuro Village is one of the majority of the population being Indonesian Migrant Workers (TKI) and Female Migrant Workers (TKW), as for the background of the large number of residents who choose to work abroad due to economic factors and the lack of jobs that can meet the needs of families in the Solokuro village. This PKM activity will provide assistance to the group of women who are retired after TKW “Sinar Berdikari Business Group” by developing a variety of home-based snack products. The solutions offered in this program are: Help increase production capacity and business marketing management, strengthen business group institutions. The solution offered in this program is by providing production tools, training in business management and marketing, facilitating the formation of business groups in a professional manner, assisting in making media marketing business information technology. The method used in this service is the training method combined using the FGD (Focus Group Discussion) method, participatory assistance. From the results of the Sinar Berdikari Business group assistance and the residents of Solokuro Lamongan, innovation needs to be made to make food made from corn with a variety of flavors and shapes to increase partner productivity, equip partners with good managerial, partners will be able to run their businesses effectively and efficiently, train good packaging methods will increase sales of partners to package a product so that it is more attractive and has high selling power, teaching partners with marketing training can increase the sales volume of partners from the local market to the national market and the need for continuous monitoring and coaching so that the business partners and residents of Solokuro Lamongan can develop accordingly hope.